2018
DOI: 10.1302/0301-620x.100b10.bjj-2017-0406.r3
|View full text |Cite
|
Sign up to set email alerts
|

Material loss at the femoral head taper

Abstract: Aims There are limited published data detailing the volumetric material loss from tapers of conventional metal-on-polyethylene (MoP) total hip arthroplasties (THAs). Our aim was to address this by comparing the taper wear rates measured in an explanted cohort of the widely used Exeter THA with those measured in a group of metal-on-metal (MoM) THAs. Patients and Methods We examined an existing retrieval database to identify all Exeter V40 and Universal MoP THAs. Volumetric wear analysis of the taper surfaces wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Third, Hothi et al found significantly less material loss from the taper‐trunnion junctions of retrieved MoP THRs compared with MoM THRs of the same design . Across different designs, Langton et al have shown that wear from the taper‐trunnion junction of MoP THRs is less than that from MoM THRs . For these reasons, material loss from the taper‐trunnion junctions of MoM hips cannot be used to predict the wear from the taper‐trunnion junctions of MoP THRs.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Hothi et al found significantly less material loss from the taper‐trunnion junctions of retrieved MoP THRs compared with MoM THRs of the same design . Across different designs, Langton et al have shown that wear from the taper‐trunnion junction of MoP THRs is less than that from MoM THRs . For these reasons, material loss from the taper‐trunnion junctions of MoM hips cannot be used to predict the wear from the taper‐trunnion junctions of MoP THRs.…”
Section: Discussionmentioning
confidence: 99%